Nueva especie de rana bromelícola del género Pristimantis (Amphibia: Craugastoridae), meseta de la Cordillera del Cóndor, Ecuador - Brito M., Jorge; Almendáriz C., Ana; Batallas R., Diego; Ron, Santiago R. (Papéis Avulsos de Zoologia, 2017)
We describe a small frog of the genus Pristimantis inhabiting bromeliads (snout-vent length 20.3‑23.3 mm in females, 16.1‑17.4 mm in males), from a remote sandstone plateau of the Cordillera del Condor, in southeastern Ecuador, with an altitudinal range of 2,045‑2,860 m. A phylogeny based on sequences of DNA (mitochondrial and nuclear genes) supports inclusion in the P. orestes group and suggests an undescribed Pristimantis from the southern slope of eastern Ecuador as the closest taxon. The new species differs from its congeners in Ecuador by having predominantly black dorsal and ventral coloration; comprehensive and robust palmar surface with stubby fingers; presence of a deep and wide groove from the anterior base of finger I to the rear base of the palmar tubercle; subarticular divided tubers, enlarged supernumerary small granules and tubercles. All individuals were found in terrestrial bromeliads. The calls are short, frequency modulated, comprising of a note 5‑15 ms in duration. Insects represented 80% of the diet of the new species.